EVALUASI EFEKTIVITAS METODE PEMBELAJARAN TEMATIK DI SMP N 21 BENGKULU: PERSPEKTIF GURU DAN SISWA - heriadi, Meddyan; dusti tatri, Ema; Rini merliana, Setia; musfika rahayu, Malinda; rotul mukasafah, Dhaq (Jurnal Ilmu Pendidikan Islam, 2025)
The thematic learning method is an approach that integrates various subjects in one particular theme to improve students' overall understanding. This research aims to evaluate the effectiveness of thematic learning methods at SMP N 21 Bengkulu from the perspective of teachers and students. The research method used is a qualitative descriptive method with data collection techniques in the form of interviews, observations and questionnaires. The research results show that the thematic learning method has advantages in increasing student involvement, but there are still obstacles in implementation, such as limited resources and teacher readiness in adapting this method. Therefore, strategies are needed to increase teacher competency and provide more adequate resources to increase the effectiveness of thematic learning in this school.